Safe genetic modification of cardiac stem cells using a site-specific integration technique - Lan, Feng; Liu, Junwei; Narsinh, Kazim H.; Hu, Shijun; Han, Leng; Lee, Andrew S.; Karow, Marisa; Nguyen, Patricia K.; Nag, Divya; Calos, Michele P.; Robbins, Robert C.; Wu, Joseph C. (Circulation, 2012)
Background-Human cardiac progenitor cells (hCPCs) are a promising cell source for regenerative repair after myocardial infarction. Exploitation of their full therapeutic potential may require stable genetic modification of the cells ex vivo. Safe genetic engineering of stem cells, using facile methods for site-specific integration of transgenes into known genomic contexts, would significantly enhance the overall safety and efficacy of cellular therapy in a variety of clinical contexts. Methods and Results-We used the phiC31 site-specific recombinase to achieve targeted integration of a triple fusion reporter gene into a known chromosomal context in hCPCs and human endothelial cells. Stable expression of the reporter gene from its unique chromosomal integration site resulted in no discernible genomic instability or adverse changes in cell phenotype. Namely, phiC31-modified hCPCs were unchanged in their differentiation propensity, cellular proliferative rate, and global gene expression profile when compared with unaltered control hCPCs. Expression of the triple fusion reporter gene enabled multimodal assessment of cell fate in vitro and in vivo using fluorescence microscopy, bioluminescence imaging, and positron emission tomography. Intramyocardial transplantation of genetically modified hCPCs resulted in significant improvement in myocardial function 2 weeks after cell delivery, as assessed by echocardiography (P=0.002) and MRI (P=0.001). We also demonstrated the feasibility and therapeutic efficacy of genetically modifying differentiated human endothelial cells, which enhanced hind limb perfusion (P<0.05 at day 7 and 14 after transplantation) on laser Doppler imaging. Conclusions-The phiC31 integrase genomic modification system is a safe, efficient tool to enable site-specific integration of reporter transgenes in progenitor and differentiated cell types. © 2012 American Heart Association, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: cardiovascular disease; cell therapy; imaging; stem cells